Soybean Development Strategy in Kasimpa Jaya Village South Tiworo District West Muna Regency - Suyanti Indramayu; Rosmawaty Rosmawaty; La Ode Kasno Arief (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
This study aims to determine soybean production and productivity in Kasimpa Jaya Village, South Tiworo District, West Muna Regency, and to find out the strategies prioritized in the development of soybean crops in Kasimpa Jaya Village, South Tiworo District, West Muna Regency. Data analysis used to determine the amount of soybean production and productivity is by quantitative descriptive analysis. The Analysis Hierarchy Process (AHP) method determines soybean crop development strategies recommendations. Eight respondents from this study were purposely determined. The results showed that soybean production produced by soybean farmers in Kasimpa Jaya Village, South Tiworo District, was 14,900 kg with an average production yield of 1,862.5 kg and productivity of 7,426.66 Kg / Ha with an average value of 928.33 Kg/ha of soybeans. The results of the analysis of the soybean crop development strategy in Kasimpa Jaya Village, South Tiworo District, West Muna Regency, based on the Analysis Hierarchy Process (AHP), can be carried out using three main priority choices based on the results of the AHP, namely the procurement of facilities to soybean farmers, assistance (extension) to soybean farmers and increasing human resources in soybean farming activities.